2004
DOI: 10.1111/j.1365-2362.2004.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐induced expression of peroxisome proliferator‐activated receptor α and activation of fatty acid oxidation enzymes in fatty liver

Abstract: Clofibrate was a more potent inducer of PPARalpha expression than HFD in our rat fatty liver model. The finding of blunted peroxisomal enzyme response to clofibrate in fatty livers suggests that alterations in postreceptor events may exist and further contribute to liver steatosis. Clofibrate seems to stabilize glutathion content and this might contribute to the prevention of liver steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 31 publications
(37 reference statements)
6
43
0
1
Order By: Relevance
“…Gemfibrozil supplemented high fat diet increased PPAR-α expression more significantly in comparison with gemfibrozil alone. This finding was supported by our previous study in which Wistar-Albino rats were fed high fat diet plus clofibrate and we reported that clofibrate alone increased PPAR-α expression more effectively in comparison with high fat diet alone [8] . However, in the previous study [8] , there was no significant difference in between clofibrate plus high fat diet and control diet supplemented with clofibrate which is differed from our present findings.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Gemfibrozil supplemented high fat diet increased PPAR-α expression more significantly in comparison with gemfibrozil alone. This finding was supported by our previous study in which Wistar-Albino rats were fed high fat diet plus clofibrate and we reported that clofibrate alone increased PPAR-α expression more effectively in comparison with high fat diet alone [8] . However, in the previous study [8] , there was no significant difference in between clofibrate plus high fat diet and control diet supplemented with clofibrate which is differed from our present findings.…”
Section: Discussionsupporting
confidence: 79%
“…PPAR-α target genes are related to the mitochondrial and peroxisomal oxidation of fatty acids and intracellular other lipid metabolisms [4,9,24] . In this context, it could be suggested that free fatty acids could induce PPAR-α expression and consequently increase oxidation of fatty acids in the liver [4,8] . Unsaturated fatty acids are natural ligands of the PPAR-γ as in PPAR-α [30] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even further, if the role of PPAR-a is to sense fatty-acid flux into cells, then a high-fat diet should trigger PPAR-a activation in tissues containing this receptor. In contrast, rats fed either normal chow or a high-fat diet display identical levels of two downstream targets of PPAR-a, acyl-CoA-dehydrogenase (ACD) -the rate-limiting enzyme of peroxisomal boxidation -and acyl-coA-oxidase (AOX) -a mitochondrial b-oxidation enzyme -indicating that an elevated fattyacid load in the liver does not alter PPAR-a function [48]. Similarly, dietary supplementation of fat to humans fails to increase fat utilization or stimulate energy balance up to 24 h following their ingestion [49,50].…”
Section: The Fatty-acid Sensor Hypothesis Revisitedmentioning
confidence: 99%